Mediocrity Madness: the Destructive Effects of Antonio Salieri’s Narcissistic Personality Disorder in Amadeus - Ivonne Muliawati Harsono (kata, 2017)
Industriousness is generally perceived as a noble trait. Such mindset is firmly ingrained within the society through religious teachings and moral virtues. Since the foundation of identity is shaped through difference, many people endure tedious labour to either arrive at a socially-approved level or surpass that level. For individuals with Narcissistic Personality Disorder, the struggle to dismiss mediocrity may result in a form of madness conveyed through destructive actions towards both the subject and the object. The purpose of this paper is to identify the phases through which Antonio Salieri’s Narcissistic Personality Disorder in Amadeus triggers a series of destructive effects aimed at himself and others. This research concludes that the transition from the sense of mediocrity to mediocrity madness for people with Narcissistic Personality Disorder can be divided into three phases: the acknowledgment of mediocrity, the narcissistic wound, and the mediocrity madness.